Investigação do mecanismo da ação antidiabética do extrato etanólico das flores de Combretum lanceolatum Pohl - Siqueira, Juliany Torres (2012)
Previous studies from our laboratory have shown the antidiabetic activity of the Combretum lanceolatum flowers ethanolic extract (ClEtOH). The treatment of diabetic rats with 500 mg/kg of ClEtOH for 21 days improved several physiological and biochemical parameters classically altered in diabetes mellitus in a similar way of the treatment with 500 mg/kg of metformin, a well known antihyperglycemic agent. Considering these results, the objective of the present study was to investigate the mechanism of action related to the antidiabetic activity of ClEtOH, mainly the actions of the extract at hepatic level. Male Wistar rats (180-200 g, 39-40 days old) were divided into the groups: normal (N) and diabetic (streptozotocin, 40 mg/kg i.v.) non-treated (DC), diabetic treated with 500 mg/kg of metformin (DMet) and diabetic treated with 500 mg/kg of ClEtOH (DT500). After 21 days of treatment, the animals were euthanized and several analysis were performed. In the serum, the insulin levels were determined through immunoenzymatic assay. In the liver, changes in the activation of AMPK and insulin intracellular signaling components and the protein levels of PEPCK were analyzed through Western blotting. Liver glucose and urea production from L-glutamine were investigated through liver in situ perfusion. The direct effect of the extract in the AMPK phosphorylation was investigated in liver slices from normal rats incubated in vitro in the absence or presence of ClEtOH, metformin or quercetin. Results were expressed as mean±S.E.M. and analyzed by one way ANOVA or unpaired t test (p<0.05; p<0.01 e p<0.001). The serum insulin levels were not changed in diabetic rats treated with ClEtOH or metformin in comparison to values found in non-treated diabetic animals. It was observed reduction in the liver glucose production in diabetic rats treated with ClEtOH (51%) or metformin (68%) in comparison to DC, as well as in the liver urea production in both groups (22%). The PEPCK protein levels were 28 and 43% decreased in liver from animals from DT500 and DMet groups, respectively, when compared to DC. The phosphorylation levels of AMPK were about 17% higher in liver from diabetic rats treated with ClEtOH or metformin when compared to DC. The increase in the AMPK phosphorylation is attributed to a direct action of the extract, since the in vitro incubation of liver slices in the presence of ClEtOH led to increase (31%) in the phosphorylation levels of AMPK, as well as the incubation with metformin (23%) or quercetin (29%), the major compound in the extract. It was an increase of 94% in the basal phosphorylation of AKT in liver from diabetic rats treated with ClEtOH, in comparison to DC group, without differences between DC and DT500 groups in the insulin-stimulated AKT phosphorylation levels. The antidiabetic activity of ClEtOH can be attributed, at least in part, to inhibition of liver gluconeogenesis, promoted by activation of AMPK and AKT and inhibition of expression of PEPCK, key enzyme of this process.